ENGAGING INDONESIAN YOUTH WITH THE MEBUUG-BUUGAN TRADITION THROUGH THE NOVEL "SEHARI SETELAH SEPI" - Danaswari, Ni Wayan Mahadewi Suci; Sutanto, Shienny Megawati (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2024)
This research explores the potential of novel illustrations as an educational medium for the Mebuug-buugantradition, a unique ritual from Kedonganan Village, Bali, which has been increasingly marginalized from the younger generation's knowledge. Through a qualitative approach, this study analyzes how the "slice of life" genre and anime/webtoon visual style can be utilized in the fictional novel "Sehari Setelah Sepi" to bridge the generational gap and promote local cultural heritage. Set in 2017-2018, when the Mebuug-buugan tradition was revived, the novel aims to present a relevant and engaging story for Indonesian teenagers. Analysis of literature, competitor research, and Unique Selling Proposition (USP) formed the foundation for designing practical illustrations. Research findings indicate that combining the "slice of life" genre with anime/webtoon visual style can effectively convey complex information about the history and meaning of the Mebuug-buugan tradition in a simple yet profound manner. The novel serves as entertainment and an effective educational tool for introducing Balinese cultural values to the younger generation.